2012
DOI: 10.1061/(asce)mt.1943-5533.0000398
|View full text |Cite
|
Sign up to set email alerts
|

Life-Cycle Cost Analysis of Alternative Reinforcement Materials for Bridge Superstructures Considering Cost and Maintenance Uncertainties

Abstract: A life cycle cost analysis (LCCA) was conducted on prestressed concrete bridges using carbon fiber reinforced polymer (CFRP) bars and strands. Traditional reinforcement materials of uncoated steel with cathodic protection and epoxy-coated steel were also considered for comparison. A series of deterministic LCCAs were first conducted to identify a range of expected cost outcomes for different bridge spans and traffic volumes. Then, a probabilistic LCCA was conducted on selected structures that included activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
36
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(36 citation statements)
references
References 21 publications
0
36
0
Order By: Relevance
“…Despite this, it is noted that due to the use of a very high percentage of RAP, experiments demonstrate that the solutions proposed meet a number of sustainability requirements [29][30][31]. Furthermore, these facts illustrate the potential and suitability of the designed mixes for improved pavement life cycles [32][33][34][35]. …”
mentioning
confidence: 99%
“…Despite this, it is noted that due to the use of a very high percentage of RAP, experiments demonstrate that the solutions proposed meet a number of sustainability requirements [29][30][31]. Furthermore, these facts illustrate the potential and suitability of the designed mixes for improved pavement life cycles [32][33][34][35]. …”
mentioning
confidence: 99%
“…A recent life-cycle cost analysis of FRP-reinforced bridges revealed that, while FRP 50 bars may be on the order of 6-8 times more expensive than steel, and the resulting cost of a 51 typical bridge superstructure reinforced with FRP may range from 25-75% higher than its steel-52 reinforced equivalent, reduced maintenance costs can be expected to result in a net cost savings 53 near 20 years of service life. Moreover, considering a 50 to 75 year time span, total life-cycle 54 costs for typical FRP-reinforced bridges were generally predicted to be one-half or less of their 55 steel-reinforced alternatives (Eamon et al 2012). Andrawes 2010).…”
Section: Structural Concrete Reinforced With Frp Bars Aci-4401r (Acmentioning
confidence: 99%
“…Texas (Eamon et al 2012). Although FRP reinforcement has been commercially available for 37 more than a decade, FRP-reinforced structures represent a small portion of new and renovated 38 concrete bridges.…”
Section: Introduction 22mentioning
confidence: 99%
“…Although relatively small in number, FRP-reinforced concrete components have been implemented throughout the world as well as in the US, where the construction of various structures have been documented in the technical literature [4]. Currently, the two prevailing US guidelines governing reinforced concrete structural design, The American Association of State and Highway Transportation Officials (AASHTO) Bridge Design Specifications [5] and the American Concrete Institute Building Code Requirements for Structural Concrete, ACI-318 [6], for bridges and buildings, respectively, do not contain detailed guidelines for the use of FRP.…”
Section: Introductionmentioning
confidence: 99%
“…However, the reduced corrosion-induced maintenance costs generally become beneficial in the long run, where life-cycle cost analyses of FRP-reinforced bridges revealed significant cost savings over a 50 to 75 year bridge lifetime, typically resulting in half or less of the total life-cycle cost of corresponding steelreinforced bridges. In the considered cases, cost savings usually began at approximately 20 years into the service life of the bridge [4]. However, with an expected 20-year pay-back period, initial cost is still a major concern, and any initial cost savings are clearly highly desirable.…”
Section: Introductionmentioning
confidence: 99%